Determination of Drinking Water Quality: A Case Study on Saline Prone South-West Coastal Belt of Bangladesh (Journal of Environmental Science and Natural Resources, 2017)
This research integrates quantitative data of underground and sub-surface sources of drinking water from two coastal union Gabura and Munshiganj of Shyamnagur upazila of Satkhira district. Four drinking water sources have been selected and sampled during dry season when the salinity rate is generally high. A total of 22 water samples have been collected of which 6 from protected pond, 6 from tube well, 6 from rainwater and 4 from pond sand filter (PSF). The average pH of tube well water, protected pond water, pond sand filter water and rain water were 6.59 (±.05), 6.46 (±1.03), 6.60 (±.52), 5.95 (±.87), respectively. The average EC (μs cm-1) range of tube well water, protected pond water, pond sand filter water and rain water were 2059.16 (±49.43), 1756 (±14), 769 (±94.27), 64.33(±59.91) while the TDS (ppm) range were 1319.97 (±31.69), 1125.64 (±913.46), 492.94 (±60.43) and 15.38 (±118.59) respectively. The maximum concentration of salinity was found in tube well water which was 1.37 (±53) ppt. Most of the protected ponds were highly contaminated with sulphate and it ranges from 84.64 to 218.25 ppm. The average number of fecal Coliform in protected ponds were 1650 100 m l-1 of water while in PSF source pond 2350 100ml-1 and collection point 1.5 100ml-1.J. Environ. Sci. & Natural Resources, 10(1): 101-108 2017